Viral Infections Exacerbate FUS-ALS Phenotypes in iPSC-Derived Spinal Neurons in a Virus Species-Specific Manner - Bellmann, Jessica; Monette, Anne; Tripathy, Vadreenath; Sójka, Anna; Abo-Rady, Masin; Janosh, Antje; Bhatnagar, Rajat; Bickle, Marc; Mouland, Andrew J.; Sterneckert, Jared (Frontiers in Cellular Neuroscience, 2019)
Amyotrophic lateral sclerosis (ALS) arises from an interplay of genetic mutations and environmental factors. ssRNA viruses are possible ALS risk factors, but testing their interaction with mutations such as in FUS, which encodes an RNA-binding protein, has been difficult due to the lack of a human disease model. Here, we use isogenic induced pluripotent stem cell (iPSC)-derived spinal neurons to investigate the interaction between ssRNA viruses and mutant FUS. We find that rabies virus (RABV) spreads ALS phenotypes, including the formation of stress granules with aberrant composition due to increased levels of FUS protein, as well as neurodegeneration and reduced restriction activity by FUS mutations. Consistent with this, iPSC-derived spinal neurons harboring mutant FUS are more sensitive to HIV-1 and Zika viruses. We demonstrate that RABV and HIV-1 exacerbate cytoplasmic mislocalization of FUS. Our results demonstrate that viral infections worsen ALS pathology in spinal neurons with genetic risk factors, suggesting a novel role for viruses in modulating patient phenotypes.